Analysis of Accident Risk Assessment on Prof. Muhammad Yamin Road Tegal Regency Using the HIRARC Method - Adrian, Ari (Universitas Pendidikan Nasional, 2025)
Prof. Muhammad Yamin Street in Tegal Regency is a primary collector road with a two-lane, two-way undivided configuration, stretching for 2.2 kilometers. This road serves as a connector between sub-districts and is frequently used by the public, especially during school rush hours. The increase in traffic activity in this area creates potential conflicts between vehicles and pedestrians, particularly students. This study aims to identify the level of traffic accident risk along this road segment. The method used is HIRARC (Hazard Identification, Risk Assessment, and Risk Control), which allows for a systematic analysis of potential hazards, risk assessment, and control strategies. Survey results indicate that the condition of road markings and traffic signs falls into the moderate-risk category, while physical road damage such as ravelling, cracking, and potholes is classified as extreme risk. Several signs were also found to be covered by vegetation or vandalized. Recommended control measures include repainting road markings, maintaining traffic signs, and repairing pavement damage. These findings are expected to contribute to tangible improvements in road safety and serve as a consideration for policymakers in managing safer and more sustainable road infrastructure.